Thyroid function and thyroid homeostasis parameters are associated with increased urinary albumin excretion in euthyroid individuals over 60 years old from NHANES - Liu, Xue; Li, Yuchen; Chai, Yuwei; Zhang, Yuhao; Zhang, Li; Zhang, Haiqing (Frontiers in Endocrinology, 2024)
The relationship between thyroid function/homeostasis parameters and renal function has been extensively studied. However, the relationship between thyroid function and thyroid homeostasis parameters with albuminuria among elderly individuals remains unclear.The population was divided into an albuminuria group and non-albuminuria group for baseline characteristic difference analysis. Multivariable logistic regression was used to test the association between thyroid function, and thyroid homeostasis parameters and albuminuria. The nonlinear relationship was explored with restricted cubic splines. Meanwhile, we investigated whether the relationship also existed in the diabetes and hypertension subgroups. Receiver operating characteristic (ROC) curves were used to assess the effectiveness of the indices.FT4 and TFQIFT4 were positively correlated with albuminuria (OR =1.12; 95% CI=1.02-1.23, P = 0.02); OR =1.79; 95% CI=1.08-2.99, P = 0.03), and FT3/FT4 was negatively correlated with albuminuria (OR =0.03; 95% CI=0.00-0.26, P = 0.003). Additionally, the nonlinear relationship Thyroid and albuminuria 3 between FT3/FT4 as well as TSHI and albuminuria was approximately U-shaped. Similar results were observed in the hypertension subgroup but not in the diabetes subgroup. There was a U-shaped nonlinear relationship between FT3 and albuminuria in the diabetes group. In addition, FT3/FT4 performed better than TFQI, TT4RI, and TSHI in ROC analyses for albuminuria prediction.FT4, TFQIFT4 and a low FT3/FT4 ratio were risk factors for albuminuria in euthyroid individuals over 60 years old. However, FT3 was more associated with albuminuria in the diabetes subgroup.TSH was not associated with albuminuria in any analysis. In our study, we attempted to provide more reasonable thyroid parameters and basis for evaluating patients with underlying albuminuria.FT3/FT4 may be used as a helpful indicator to predict albuminuria and provide novel ideas for the evaluation and treatment of albuminuria.